PENGARUH HIJAMAH TERHADAP KADAR ERITROSIT DAN HEMATOKRIT DARAH VENA ORANG SEHAT - Lilik Pranata (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2018)
Hijamah is a treatment technique, based on the tradition that has been practiced by humans since time immemorial, now the treatment has been modernized and adjusted and follows scientific principles by using practical, sterile and effective tools, hijamah is done to remove blood dangerous from inside the body through puncture on the surface of the skin, the aim of the study was to determine the effect of hijamah on erythrocyte levels and hematocrit of venous blood of healthy people. South while blood collection was carried out at the South Sumatra Provincial Center for Health Laboratory (BBLK), the study sample was 30 people with healthy conditions, aged 18 to 22 years, this study was conducted 8 hours after hijamah treatment, the results of the study were significant differences after doing hijamah on venous blood erythrocyte levels of healthy people with a p value of 0.012, while at hematocrit levels there was a statistically significant difference in hematocrit levels of healthy venous blood with p value 0.001. Hijamah affects levels of erythrocytes and hematocrit, hijamah can be used in alternative and complementary medicine